Achieving high mass loading of Na3V2(PO4)3@carbon on carbon cloth by constructing three-dimensional network between carbon fibers for ultralong cycle-life and ultrahigh rate sodium-ion batteries. (March 2018) - Guo, Donglei; Qin, Jinwen; Yin, Zhigang; Bai, Jinman; Sun, Yang-Kook; Cao, Minhua
Abstract: The mass loading of the active materials in most flexible electrodes is relatively low, which greatly impedes their practical application. Here, we report a facile strategy to achieve high mass loading of Na3 V2 (PO4 )3 @carbon (NVP@C) supported on carbon cloth (NVP@C-CC) by a two-step coating followed by an annealing treatment and the resultant NVP@C-CC membrane can be used as a binder-free cathode for sodium ion batteries (SIBs). The NVP@C is not only uniformly anchored on the surface of carbon fibers of CC, but also filled between carbon fibers of CC in interconnected three-dimensional (3D) macroporous structure. It is because of the full use of the spaces between carbon fibers of CC that we achieve a high NVP@C mass loading. Thus-obtained NVP@C-CC exhibits excellent cyclability (82.0% capacity retention over 2000 cycles at 20 C) and high rate capacity (96.8 mA h g −1 at 100 C and 69.9 mA h g −1 at 200 C) for sodium half cells and meanwhile the high mass loading of NVP@C on CC also endows the cell with fairly high energy and powder densities of 396 W h kg −1 and 97 kW kg −1 . Furthermore, it also presents superior cycling stability and rate performance when evaluated as full battery (NaTi2 (PO4 )3 @C as the anode) cathode. This study offers a new strategy for achieving high mass loading of the active materials on flexible supports in flexible energy storage devices. Graphical abstract: The NVP@C-CC electrode with high mass loading was achieved by contructing three-dimensinal network among carbon fibers. The NVP@C-CC electrode exhibits excellent cycling performance and superior rate capacity for both sodium half cells and full cell cathode (NaTi2 (PO4 )3 @C as the anode). To further demonstrate its potential application, the as-prepared full cell can easy to power commercial red light-emitting diode bulb after being fully charged.fx1 Highlights: A two-step coating strategy is used to prepare NVP@C-CC electrode with high mass loading. The high mass loading is attributed to the full use of the spaces among carbon fibers by contructing three-dimensinal network. The NVP@C-CC exhibits excellent cycling performance and superior rate capacity for both sodium half cells and full cells.